Search for associated Higgs boson production using like charge dilepton events in pp̄ collisions at √s=1.96TeV - Abazov, V. M. (2011)
We present a search for associated Higgs boson production in the process pp̄→W/ZH→±′ ±+X in ee, eμ, and μμ final states. The search is based on data collected by the D0 experiment at the Fermilab Tevatron Collider at √s=1.96TeV corresponding to 5.3fb-1 of integrated luminosity. We require two isolated leptons (electrons or muons) with the same electric charge and additional kinematic requirements. No significant excess above background is observed, and we set 95% C.L. observed (expected) upper limits on ratio of the production cross section to the standard model prediction of 6.4 (7.3) for a Higgs boson mass of 165 GeV and 13.5 (19.8) for a mass of 115 GeV. © 2011 American Physical Society.